Impact of anemia management with EPO on psychologic distress in cancer patients: results of a multicenter patient survey. (January 2014) - Del Prete, Salvatore; Cinieri, Saverio; Lorusso, Vito; Maiorino, Luigi; Pizza, Carmine; Pisano, Agata; Montesarchio, Vincenzo; Leo, Luigi; Savastano, Clementina; Pistolese, Giuseppe; Bianco, Maddalena; Mabilia, Roberto; et al.
ABSTRACT: Aim: We investigated the role of erythropoietin (EPO) in reducing anemia and preventing the development of psychological distress in patients treated with chemotherapy.Patients & methods: This prospective observational study enrolled 591 adult patients receiving EPO at a dose of 30, 000 IU administered once weekly for chemotherapy-induced anemia (mean baseline hemoglobin [Hb] level was 9.55 g/dl) over a 12-month period.Results: The majority of patients (371 [71%] patients) achieved a Hb increase >2 g/dl after 4 weeks of treatment. Interestingly, the nonresponder group had a statistically significant deterioration of their psychological conditions as indicated by psychological distress score (p = 0.01). However, within the group of responders to EPO, the Psychological Distress Inventory score remained unchanged. In the present study, severe side effects associated with EPO were not recorded.Conclusion: Hb increase, induced by EPO, ameliorates the psychological conditions of cancer patients.